Biodegradable and Bioactive PCL–PGS Core–Shell Fibers for Tissue Engineering - Hou, Lijuan (ACS Omega, 2017)
[Image: see text] Poly(glycerol sebacate) (PGS) has increasingly become a desirable biomaterial due to its elastic mechanical properties, biodegradability, and biocompatibility. Here, we report microfibrous core–shell mats of polycaprolactone (PCL)–PGS prepared using wet–wet coaxial electrospinning. The anticoagulant heparin was immobilized onto the surface of these electrospun fiber mats, and they were evaluated for their chemical, mechanical, and biological properties. The core–shell structure of PCL–PGS provided tunable degradation and mechanical properties. The slowly degrading PCL provided structural integrity, and the fast degrading PGS component increased fiber elasticity. Young’s modulus of PCL–PGS ranged from 5.6 to 15.7 MPa. The ultimate tensile stress ranged from 2.0 to 2.9 MPa, and these fibers showed elongation from 290 to 900%. The addition of PGS and grafting of heparin improved the attachment and proliferation of human umbilical vein endothelial cells. Core–shell PCL–PGS fibers demonstrate improved performance as three-dimensional fibrous mats for potential tissue-engineering applications.